PERANAN, FUNGSI, DAN TAHAPAN PENGEMBANGAN KURIKULUM PAI SEBAGAI TRANSFORMASI STRATEGIS MENUJU PENDIDIKAN YANG ADAPTIF - M. Ilham Fikron; Nanang Budianto; Achmad Muzammil (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2026)
This paper examines the role, functions, and stages of Islamic Religious Education (PAI) curriculum development toward adaptive education. The PAI curriculum plays conservative (preserving values), creative (innovation), and critical (social filter) roles. Strategically, the curriculum addresses digital disruption and globalization challenges through integrating religious moderation (wasathiyyah), digital literacy, and balancing tradition-modernity. Functionally, the curriculum serves as student guidance, an educators' operational baseline, and society's quality assurance. Its development cycle includes planning, design, implementation, and evaluation. This study also analyzes the transition from the 2013 Curriculum to Kurikulum Merdeka, despite facing challenges like teacher readiness and digital infrastructure gaps. A mature PAI curriculum is vital to produce an intelligent and noble generation.